1914
DOI: 10.1039/ct9140500609
|View full text |Cite
|
Sign up to set email alerts
|

LXI.—The decomposition of carbamide

Abstract: Most experiments were made in duplicate, and the mean value (A-x)~ was taken in calculating the constant k..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1924
1924
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Urea is unusually stable due to its resonance stabilization (estimated to be 30−40 kcal/mol), making the hydrolytic decomposition a very slow reaction. Its experimental determination is further complicated by the existence of a competitive reaction, in which urea decomposes unimolecularly, to give isocyanic acid and the ammonium ion. ,,, Because the latter is favored at any pH, the hydrolytic decomposition of urea has never been observed. In spite of this, research has been carried out, ,,, ,, in part to determine the proficiency of urease and related amidohydrolases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urea is unusually stable due to its resonance stabilization (estimated to be 30−40 kcal/mol), making the hydrolytic decomposition a very slow reaction. Its experimental determination is further complicated by the existence of a competitive reaction, in which urea decomposes unimolecularly, to give isocyanic acid and the ammonium ion. ,,, Because the latter is favored at any pH, the hydrolytic decomposition of urea has never been observed. In spite of this, research has been carried out, ,,, ,, in part to determine the proficiency of urease and related amidohydrolases.…”
Section: Resultsmentioning
confidence: 99%
“…Acid -Catalyzed Hydrolysis. Similar to the base-catalyzed reaction, the acid-catalyzed hydrolysis of urea follows an elimination reaction to give isocyanic acid and NH 4 + . ,, , No experimental or theoretical studies have been reported for the hydrolytic decomposition pathway to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…(2) After 15 minutes (see Experimental) three were removed and quenched. (3) The other samples were allowed to run 15 additional minutes. ( 4) All the samples were analyzed and the ammonium ion concentration found in the blank (step 2) was subtracted from that found in the sample (step 3).…”
Section: Resultsmentioning
confidence: 99%
“…A consideration of the literature on the rate of decomposition of urea (Armstrong & Horton, 1912;Burrows & Fawsitt, 1914;E. A. Werner, 1918;Price, 1919) shows divergence of opinion due to lack of understanding of the structure of urea.…”
Section: Reaction Group 3 Decomposition Of Ureamentioning
confidence: 99%